Preconceito e Contato Intergrupal: Um estudo dos Núcleos de Apoio as Pessoas com Necessidades Específicas - Esteves Neto, Hildebrando (2014)
In the face of globalization and international agreements, the politics of the Brazilian government began to prioritize in their educational system, care for the disabled in regular classes in regular education - National Education Plan (Goal 4, 2012). Then comes a new scenario in daily school where the social aspect of relations, prejudice has a prominent place. In this context, deploying up promoting public policies aimed at inclusion of equal opportunities and conviviality. Thus, the aim of this study was to investigate prejudice and intergroup contact in the Nucleus of Support to People with Special Needs (NAPNE's) related to educational inclusion in regular class. To accomplish this, was justified as the theoretical reflections extend toward theory of prejudice, which this work appropriates the knowledge about the theory of social representations conveyed in this medium - public politics of inclusion - the light of the theory of contact and of intergroup relations, understanding that strategies based on contact can open new horizons in terms of trade that exists between what is intrapsychic, interpersonal, intergroup or societal. The sample comprised 118 members - teachers and administrators - the inclusion of core TECNEP/ SETEC/ MEC program called NAPNE s, the Brazilian Federal Institutes, with 75,4% female, 41,5% aged 30 - 39 years old, with less than 10 years of professional experience (58,5%) , and 70,3% prepared to work with the disabled. We used the descriptive method with qualitative and quantitative explanatory approach with a descriptive character. The instrument used was a semi-structured questionnaire addressing aspects of performance; support received, the degree of satisfaction with the facilities and the main difficulties or obstacles. Variables were measured on the Likert scales and Bogardus (1925), and finally, sociodemographic questions. These data were processed using the SPSS software and EVOC, and analyzed using descriptive statistics. The results showed 70,3% of members participating in intergroup relations, but 85,6% dissatisfied with school facilities and only 14,4% satisfied with the institutional support received, at the school for lack of contact in relationships (90,6%) with Persons with Special Needs showing almost nonexistent. Segregation was rejected (92,3%). In referring to the results of the analysis means a lack of support of all kinds to the cores, nonexistent effective contact, members are eager to participate in the process agreeing with the commonality of the room, and that the public politics of inclusion in the way is causing institutional bias, allowing for operational adjustments. Research shows that the way to bring effects that would result in decreased bias in the ratio of acceptable cultural and social differences in modern society is the planned and structured intergroup contact, and that the cores can influence the process of inclusion when there are more frequent in intergroup contacts.